Diagnostic study and meta-analysis of C-reactive protein as a predictor of postoperative inflammatory complications after pancreatic surgery - Warschkow, René; Ukegjini, Kristjan; Tarantino, Ignazio (Journal of hepato-biliary pancreatic sciences, 2012)
Purpose Although C-reactive protein (CRP) can be measured by a standard blood test, its diagnostic value for distinguishing patients with inflammatory complications after pancreatic surgery from patients with normal postoperative inflammatory responses has not been adequately investigated. This study aimed to assess the diagnostic accuracy of CRP levels for the occurrence of postoperative inflammatory complications after pancreatic surgery. Methods Clinical data and CRP levels measured in 280 patients after pancreatic surgeries (performed between 1998 and 2010) until postoperative day 10 (POD 10) were retrospectively analyzed. Using the receiver operating characteristic method, diagnostic accuracy was evaluated by an area under the curve (AUC) analysis. Furthermore, the results of the present study were compared to previously published reports by applying diagnostic meta-analysis techniques. Results The 30-day mortality rate was 3.9% (95% CI 2.1—7.0%). Inflammatory complications occurred in 153 of 280 patients (54.6%; 95% CI 48.8—60.4%). On POD 4, the AUC was 0.67 (95% CI 0.58—0.76). The highest diagnostic accuracy was observed on POD 7 (AUC 0.77; 95% CI 0.68—0.85). In a diagnostic meta-analysis that included two additional studies, the diagnostic sensitivity on POD 4 was 0.63 (95% CI 0.50—0.76), and the specificity was 0.79 (95% CI 0.71—0.88). The highest sensitivity occurred on POD 6 (0.75; 95% CI 0.68—0.82). Considerable statistical heterogeneity was observed in the analysis of PODs 3, 4 and 5. Conclusion According to this limited evidence, CRP levels had a low to moderate diagnostic accuracy. Large, blinded studies are warranted for a more precise estimation of CRP's diagnostic value.